Performance investigation of compression ignition engine using empirical correlation for burning duration - Kumar A.; Tirkey J.V.; Shukla S.K. (My University, 2025)
Fuel burning rate plays a major role in optimizing the performance of internal combustion engine with reduced emission. In an attempt to optimize the performance of internal combustion engine, a novel empirical correlation is developed for fuel burning duration in tune with the methodology proposed by an earlier investigator for spark-ignition engine. The correlation was integrated with the quasi- dimensional mathematical model to analyse the combustion, performance and emission characteristics of engine. Engine speed and fuel injection timing were varied to assess the performance and corresponding exhaust emission of engine. Predictions relating to variation of burning duration with compression ratio at different equivalence ratios are in reasonable agreement with the published data on burning duration. The simulated results show that the optimum injection timing lies in the range of 23 °bTDC to 13 °bTDC for brake power and indicated power both, and the lowest brake specific fuel consumption and indicated specific fuel consumption were found close to 13 °bTDC. A sharp decrease in peak cylinder pressure was also observed with retarding injection timing, whereas both the retarding injection timing and increased engine speed accrue to reduced nitric oxide exhaust at exhaust valve open. © 2018 Society of Thermal Engineers of Serbia.